Civic identity development: ontogenetic aspect - Petrovska, Inha (Social Welfare: Interdisciplinary Approach, 2019)
Civic identity is developed through the information-perceptual, content-normative, value-semantic and integration-identification stages. It was identified (at the theoretical and empirical levels) that the basic factors of the civic identity development at its various stages are basic interpersonal needs; basic beliefs; the values of the parental family; civic attitudes of reference persons; social integration (experience of interpersonal relationships with peers); value-semantic orientations; subjectness activity; prosocial focus; social trust (including institutional); the fact of meeting the needs of physical and social existence in the state (level of social frustration); experience of interaction with the state in the form of its various agencies.